The Efficacy and Safety of Topiramate in the Prevention of Pediatric Migraine: An Update Meta-Analysis - Wu, Xinwei; Zhang, Yan; Lu, Mei; Yu, Xiaolin; Ye, Xiang; Wang, Xingbang; Shan, Peiyan (Frontiers in Pediatrics, 2020)
Abstract Background: Migraine is the most common acute primary headache in children and adolescents. In 2014, topiramate became the first preventive drug for migraine approved by the Food and Drug Administration (FDA) in adolescents. This meta-analysis was aimed to evaluate the efficacy and safety of topiramate for the prevention of pediatric migraine. Methods: We searched the PubMed, EMBASE, Cochrane Library and Chinese National Knowledge Infrastructure (CNKI) databases up to June 2019 for eligible randomized controlled trials (RCTs). The primary outcomes were mean migraine days per month, ≥50% reduction rate, and PedMIDAS scores. RevMan5.3 software was performed for statistical analysis. Results: Over all, 5 RCTs recruiting 531 patients were included in the meta-analysis. Our results demonstrate that participants receiving topiramate had a significant advantage in remitting the monthly migraine days than those receiving placebo, with an MD of -0.78 (n= 531, 95% CI -1.23 to -0.32, Z=3.37, P = 0.0008). Topiramate could also reduce the mean PedMIDAS scores (n= 238, 95% CI -16.53 to -0.49, Z=2.43, P = 0.04). However, there was no significant difference in the percentage of patients experiencing a≥50% reduction in monthly headache days between topiramate and placebo groups (n=531, 95% CI 0.94 to 1.77, Z=1.58, P = 0.11). Topiramate was associated with higher rates of side effects such as weight decrease(n=395, 95% CI 2.73 to 22.98, Z=3.81, P＜0.01) and paresthesia (n=531, 95% CI 3.05 to 13.18, Z=4.94, P＜0.01). Conclusions: Topiramate can significantly decrease monthly headache days and migraine-related burden in migraine patients less than 18 years old. However, it failed to increased 50% response rate. Adverse events seem to be more frequent in topiramate-treated children.